Dinamika Pilihan Masyarakat Pulosari Jambon terhadap Lembaga Pendidikan Islam - Khotimah, Khusnul; Mariana, Mariana (Global Education Journal, 2024)
This research aims to reveal the dynamics of the Pulosari Jambon community's choice of Islamic educational institutions, with a focus on encouraging and inhibiting factors. Choosing an Islamic educational institution is a complex decision and is influenced by various aspects. Therefore, this research was conducted to gain a deeper understanding of the factors that influence people's choices regarding Islamic educational institutions in the region. The research method used is a qualitative study with a phenomenological approach. Data was collected through in-depth interviews with various respondents including parents, teachers, and community leaders. Apart from that, participatory observation was also carried out to get a more comprehensive picture of the dynamics of the community's choice of Islamic educational institutions. The results of the research show that there are several driving factors that influence the Pulosari Jambon community in choosing Islamic educational institutions, including the quality of education, religious values, and the reputation of the institution. On the other hand, several inhibiting factors were also found, such as limited resources and travel distance. In addition, public perception of the curriculum and teaching methods also plays an important role in the decision-making process.